PELATIHAN PENGOLAHAN ROTI MANIS DAUN KELOR SEBAGAI KULINER KHAS DESA TAMBONG BANYUWANGI - Rudi Tri Handoko; Eka Afrida Ermawati; Siska Aprilia Hardiyanti (LPPM Universitas Bina Bangsa, 2023)
Tambong Village is divided into 3 hamlet areas, namely Krajan, Kejoyo, and Kebonsari. Tambong Village has potential to be developed as cultural tourism, nature tourism, and educational tourism. The training program for making sweet bread made from moringa leaves for the community as a typical culinary in Tambong Village is expected to be able to overcome the problem of low skills in developing culinary products which impact on tourist needs/satisfaction. The selection of moringa as the ingredient because thi plant can be easily found on this area because the majority of local residents make moringa leaves as a vegetable menu. Whereas, moringa leaves can also be processed into sweet bread. By giving this training, it is expected that the Politeknik Negeri Banyuwangi can participate in solving partner problems by improving community skills in developing culinary products in Tambong Village